Dancing hands : a story of friendship in Filipino sign language - Que, Joanna; Marquez, Charina (Chronicle Books LLC, 2023)
Sam is fascinated by her new neighbors and their ability to talk with their hands, and when she meets Mai, she starts to learn Filipino sign language so they can communicate. Includes dictionary of Philippine signs.